Les Enjeux ekphrastiques de la montagne à l’époque romantique - Michel Morel (Anglophonia)
The notion of Ekphrasis is here enlarged to include the reciprocal creation of text by image and image by text, a discourse that both states what it sees, and makes us see; in itself a transhistoric process necessarily assuming historical contents, in the present case Romantic ones. A paradigmatic change in values occurs at the time, the sense of discrepancy of which allows one to become aware of what is inevitably hidden by the common run of things. Indeed, a unified thematic prevails, clearly evinced in four extracts selected from contemporary works: a) The Prelude (Wordsworth); b) The Mysteries of Udolpho (Mrs Radcliffe); c) Waverley (Scott); d) Frankenstein (Mary Shelley). Their versions of mountains seem to belong to a clichéd contemporary discourse, the outlook of the first three being more retrospective, while the fourth tends to the prospective. What is at stake is a fascination tainted with fear, even horror (the sublime): an archetypal experience, here anatomised by Wordsworth, whose fundamentals are somehow shifted in terms of axiology—from the negative to the positive— in Frankenstein. The ekphrastic mediation thus serves as a catalyst for a whole contemporary culture seized in its very mutation, at the same time as it foregrounds the other fundamental dimension of mountains, the illumination and the sense of distance promised, if not granted, to the climber, in the here and now